Neonatal group B streptococcal infection : Incidence and clinical manifestation in Siriraj Hospital - Panitan Yossuck (2018)
From 1996 to 2001, nineteen episodes of bacteremia due to group B Streptococci (GBS) were diagnosed in Siriraj Hospital, Mahidol University. The incidence of early onset group B streptococcal disease (EOD) was 0.27 cases/1,000 live births in 1996, and decreased to 0.10 cases/1,000 live births in 2001. The incidence of the late onset disease (LOD) was 0.05 cases/1,000 in 1996, and there has been none since 1998. All of the infants were inborn. Low birth weight was found in 53 per cent of the infants. Fifty-eight per cent of infants were male. Forty-seven per cent of the infants were bom prematurely. None of the mothers had antenatal GBS screening. Only one mother received one dose of intrapartum antibiotic prophylaxis. No risk factor could be identified in 72 per cent of the mothers. EOD accounted for 79 per cent of all infants with GBS infections, with a mortality rate of 40 per cent. All of them died within the first 72 hours of life. Most EOD infants developed disease manifestations within 12 hours of life. Most common clinical manifestations were respiratory distress (74%), temperature instability (68%), cyanosis (63%), hypotension (42%) and lethargy (42%). Only one infant with EOD had meningitis. There were two infants in the LOD group; one of whom had cellulitis, and the other had meningitis. Neutropenia was noted in 42 per cent of all infants. Radiographic studies suggested a diffuse reticulogranular pattern or ground glass appearance in 38 per cent. The chest X-ray was interpreted as normal in 25 per cent of the infants. In conclusion, the incidence of GBS infection in newborn infants in Thailand is still very low but with a very high mortality. Prematurity accounts for almost half of the cases. Even though antepartum screening with intrapartum antibiotic chemoprophylaxis has been recommended in developed counties, its benefit and cost needs to be further investigated in Thailand.